2008
DOI: 10.1128/iai.00732-07
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role for Toll-Like Receptors in Interaction ofFasciola hepaticaExcretory/Secretory Products with Bovine Macrophages

Abstract: Alternative activation of macrophages (M) during helminth infection is a characteristic feature of the host immune response. Alternatively activated macrophages (AAM) are distinguished from others by high arginase 1 (Arg-1) activity, low nitric oxide (NO), and high interleukin 10 (IL-10) production. In murine models, these cells have been shown to possess anti-inflammatory properties. They have also been implicated in exacerbating a subsequent infection with a secondary pathogen. In this study we used cattle e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 32 publications
(44 reference statements)
5
62
0
Order By: Relevance
“…Similarly, we have found that peritoneal cells from rats cultured in the presence of ESP or a purified protein-glutathione transferase, inhibit nitric oxide production induced by the TLR4 ligand, LPS [38]. Coincidently, other authors have shown that ESP from F. hepatica reduce the ability of bovine macrophages to produce nitric oxide (NO) or IFN-induced by LPS [39]. Also, the purified protein derivatives from Mycobacterium bovis (PPD-B), which are TLR 4 and 2 ligands, induce a rise in IL-10 production [39] (Fig.…”
Section: Helminth Infections: All Roads Lead To Alternatively Activatmentioning
confidence: 85%
“…Similarly, we have found that peritoneal cells from rats cultured in the presence of ESP or a purified protein-glutathione transferase, inhibit nitric oxide production induced by the TLR4 ligand, LPS [38]. Coincidently, other authors have shown that ESP from F. hepatica reduce the ability of bovine macrophages to produce nitric oxide (NO) or IFN-induced by LPS [39]. Also, the purified protein derivatives from Mycobacterium bovis (PPD-B), which are TLR 4 and 2 ligands, induce a rise in IL-10 production [39] (Fig.…”
Section: Helminth Infections: All Roads Lead To Alternatively Activatmentioning
confidence: 85%
“…In contrast, macrophages activated by the interleukin-4 (IL-4)-dependent signal pathway are classified as alternatively activated macrophages (AAM) (14). The effects of F. hepatica tegumental antigen and excretory-secretory products on macrophages derived from mice, cattle, and ovines have been well documented (14,16,19,20,32,33). Moreover, recombinant versions of the parasite peroxiredoxin have been shown to induce the alternative activation of macrophages, as indicated by an in- A 492 nm a n t i -F h 1 5 a n t i -F h T g a n t i -E S P The ELISA plates were coated with 15 g/ml Fh12.…”
Section: Discussionmentioning
confidence: 99%
“…crease in arginase activity in murine (14,19) and ruminant (16,20) models. Recently, a homogenate of adult flukes has also been shown to induce arginase activity in bovine macrophages derived from nonvaccinated animals and cultured in vitro (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We stimulated BOMA monocytes/macrophages with Fh-ES what resulted in no TNF-α change, but LPS activated BOMA cells diminished release of TNF-α after Fh-ES stimulation. Flynn and Mulcahy (2008) proved that blood mononuclear cells stimulated with Fh-ES release IL-4 in a time related manner after infection. In the beginning of the infection no IL-4 was observed, the level of IL-4 reached its highest point in 2 nd or 6 th week and was decreasing until the 12 th week, when the infection became chronic.…”
Section: Discussionmentioning
confidence: 99%